Leadership - White, Marian Iszatt; Saunders, Christopher (Oxford University Press, 2017)
This accessible and comprehensive textbook draws on the reader's own experience of leadership in an employment context. The text adopts a critical and thematic approach to the discussion of core debates and emerging topics, while offering a wealth of case studies and other learning tools to help students put leadership theory into practice